Carboxylation of a Palladacycle Formed via C(sp3)−H Activation: Theory‐Driven Reaction Design. Issue 24 (28th October 2021) - Kanna, Wataru; Harabuchi, Yu; Takano, Hideaki; Hayashi, Hiroki; Maeda, Satoshi; Mita, Tsuyoshi
Abstract: Theory‐driven organic synthesis is a powerful tool for developing new organic transformations. A palladacycle(II), generated from 8‐methylquinoline via C(sp 3 )−H activation, is frequently featured in the scientific literature, albeit that the reactivity toward CO2, an abundant, inexpensive, and non‐toxic chemical, remains elusive. We have theoretically discovered potential carboxylation pathways using the artificial force induced reaction (AFIR) method, a density‐functional‐theory (DFT)‐based automated reaction path search method. The thus obtained results suggest that the reduction of Pd(II) to Pd(I) is key to promote the insertion of CO2 . Based on these computational findings, we employed various one‐electron reductants, such as Cp*2 Co, a photoredox catalyst under blue LED irradiation, and reductive electrolysis ((+)Mg/(−)Pt), which afforded the desired carboxylated products in high yields. After screening phosphine ligands under photoredox conditions, we discovered that bidentate ligands such as dppe promoted this carboxylation efficiently, which was rationally interpreted in terms of the redox potential of the Pd(II)‐dppe complex as well as on the grounds of DFT calculations. We are convinced that these results could serve as future guidelines for the development of Pd(II)‐catalyzed C(sp 3 )−H carboxylation reactions with CO2 . Abstract : Theory‐driven synthetic approaches represent highly efficient strategies for developing new organic transformations. We herein disclose a new carboxylation method of a stable five‐membered palladacycle(II) with CO2 . Initially, we computationally investigated potential carboxylation pathways to reveal that the reduction of Pd(II) to Pd(I) is crucial to promote the insertion of CO2 . Based on the computational results, we conducted experiments by using a one‐electron reductant such as Cp*2 Co, a photoredox catalyst, and electrolysis to obtain the targeted product in up to 90% yield.